Comparison of Endoscopic Ultrasound-Guided Fine-Needle Aspiration and Biopsy Device for Lymphadenopathy. (15th April 2021) - Tanisaka, Yuki; Mizuide, Masafumi; Fujita, Akashi; Ogawa, Tomoya; Araki, Ryuichiro; Suzuki, Masahiro; Katsuda, Hiromune; Saito, Youichi; Miyaguchi, Kazuya; Tashima, Tomoaki; Mashimo, Yumi; Yasuda, Masami; et al.
Abstract : Background . Accurate diagnosis of benign and malignant lymphadenopathy is important for determining the appropriate treatment and prognosis. This study evaluated the diagnostic accuracy and usefulness of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) with a conventional needle compared to endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) with a Franseen needle for diagnosing lymphadenopathy. Methods . Patients who underwent EUS-FNA or EUS-FNB for mediastinal or abdominal lymphadenopathy between July 2013 and August 2020 were enrolled in the study. The outcomes between EUS-FNA patients (July 2013 to January 2017; 22-gauge conventional needle; Group A) and EUS-FNB patients (February 2017 to August 2020; 22-gauge Franseen needle; Group B) were compared. Results . A total of 154 patients (Group A: 83; Group B: 71) were analyzed. The diagnostic accuracy (differentiating between malignant and benign lesions) was 88.0% (95% confidence interval [CI], 79.2–93.3%) in Group A and 95.8% (95% CI, 88.3–98.8%) in Group B. Group B had high diagnostic accuracy, but there was no difference between the groups (p = 0.14 ). Group B had significantly fewer passes (median 2, interquartile range (IQR): 2-4) than Group A (median 3, IQR: 3-4) (p < 0.001 ). No procedural adverse events occurred in either group. Conclusions . Although the diagnostic accuracy between the groups was not statistically significant, EUS-FNB with a Franseen needle provided high diagnostic accuracy and required fewer passes to establish a diagnosis. Thus, EUS-FNB is useful for diagnosing lymphadenopathy.